FUNGSI BUAH DAN DAUN TANAMAN DALAM BUDAYA BALI SEBUAH KAJIAN TERHADAP TANAMAN UPACARA - Adiputra, I Nyoman (Bumi Lestari; Vol 17 No 2 (2017)DO - 10.24843/blje.2017.v17.i02.p03, 2017)
According to the Balinese culture, there are some classifications of plants, such as: medicinal plants, ceremonial plants, commodity plants, horticulture, and magical plants. Due to it’ very importance value, culturally, there is a special day for the existing plants, called tumpek uduh , where a special offering is intended to the god of plantation. In this article is drawn function of leaves and fruits as a material for offering. Analysis is focused on the use of fruits as pala gantung , pala bungkah or tuber for the offerings to the god. The leaves are used for religious ceremony in term of panca dhala or asta dala . In composing the offerings, there is a guidance derived from tatwa pangider-ideran (point of compass). The used of leaves and fruits, is based on the color of leaves and fruits. The goals are for preserving/ conserving and peace-full fitting of nature. The liquid of young coconut fruits are used for the process of purifications materials, places, and the symbols of religious matters. Starting from east direction: nyuh bulan , east-south: nyuh rangda , south direction: nyuh udang , south west: nyuh surya , west direction: nyuh kuning , west-north: nyuh be julit , north direction: nyuh mulung , and the middle: nyuh sudamala . That is the respective-, dedicative offerings from human being to the nature by making use of materials for the feacefull, safety, and sustainability of the nature itself.